1982
DOI: 10.1210/endo-110-6-1885
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Haloperidol Treatment Increases the Level of in Vitro Translatable Messenger Ribonucleic Acid Coding for the β-Endorphin/drenocorticotropin Precursor Proopiomelanocortin in the Pars Intermedia of the Rat Pituitary

Abstract: Chronic treatment of rats with haloperidol (1.5 mg/kg, once daily) over a period of 7--21 days resulted in a 80--100% increase in the tissue levels of immunoreactive beta-endorphin and in the in vitro release of immunoreactive beta-endorphin from the neurointermediate pituitary. Incorporation of [3H]phenylalanine into isolated neurointermediate pituitaries of haloperidol-treated rats revealed an increase in the amount of label incorporated into the beta-endorphin/ACTH precursor proopiomelanocortin (POMC) to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

1983
1983
1997
1997

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…These 3'-tailed probes hybridized with the same anatomical specificity as the 5'-labeled probe, regardless of tail length, indicating that longer tails should be used to increase probe specific activity. Furthermore, the 3H-labeled probe gave a strong discrete hybridization signal from cells in the pituitary anterior lobe, as reported previously for 3H-labeled POMC cDNA (14 (3,4,19), was also confirmed on a series of alternate tissue sections with a longer POMC cDNA. The high correlation (r = 0.96) between the hybridization OD values obtained using the two probes confirms the accuracy of the oligonucleotide probe in detecting a predicted change in mRNA levels.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…These 3'-tailed probes hybridized with the same anatomical specificity as the 5'-labeled probe, regardless of tail length, indicating that longer tails should be used to increase probe specific activity. Furthermore, the 3H-labeled probe gave a strong discrete hybridization signal from cells in the pituitary anterior lobe, as reported previously for 3H-labeled POMC cDNA (14 (3,4,19), was also confirmed on a series of alternate tissue sections with a longer POMC cDNA. The high correlation (r = 0.96) between the hybridization OD values obtained using the two probes confirms the accuracy of the oligonucleotide probe in detecting a predicted change in mRNA levels.…”
Section: Resultssupporting
confidence: 86%
“…As a final test ofoligonucleotide probe specificity and to provide initial data on the usefulness of these probes in detecting the effects of in vivo treatment, pituitary sections from haloperidol-treated and control rats were hybridized with the 32P-labeled oligonucleotide or cloned cDNA probes used previously. As expected from previous studies (3,4,19), the hybridization signal in the Unlabeled ) is included as a control for specificity. The oligonucleotide was 32P-labeled at the 5' or 3' terminus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that in addition to having effects on POMC peptide secretion, dopaminergic compounds can also change IP content of POMC peptides (3,9). Chronic treatment of the rat with dopamine agonists or antagonists either decreases or increases, respectively, the amount of radioimmunoactive ,3endorphin or a-MSH in the IP.…”
mentioning
confidence: 99%
“…As a result, dopamine receptor agonists inhibit and antagonists stimulate the biosynthesis and release of 8-endorphin (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%